Co-composting of municipal sewage sludge and landscaping waste using pilot scale system and application of compost to an ornamental plant, (Tagetes erecta L.) - Dzulkarnain, Zulnaim (2016)
A high-value product with nutrient-rich organic matter namely biocompost can be produced from renewable biomass materials such as municipal sewage sludge and landscaping waste. In Malaysia, these materials are still not being utilized completely. By using aerobic fermentation, production of biocompost from these materials can be done. The objectives of this research are: (1) to investigate the effectiveness of pilotscale windrow and bioreactor systems for co-composting of municipal sewage sludge and landscaping waste; and (2) to evaluate the potential of biocompost from municipal sewage sludge and landscaping waste in windrow and bioreactor systems on the growth performance of a selected ornamental plant, Tagetes erecta. Co-composting process was carried out using different systems (windrow and bioreactor) with monitoring for the crucial parameters for composting such as temperature, oxygen level, moisture content and pH. Proximate and ultimate analysis of the product produced were determined to evaluate the process performance. Planting trial was conducted using an ornamental plant Tagetes erecta, with an experimental design using Randomized Complete Block Design (RCBD) method. The plant was applied with different types of fertilizer, using inorganic fertilizer as a control to compare with biocompost from windrow and bioreactor system. The plant and soil (before and after treatment) were analysed physically and analysis was done using statistical analysis software, Statistical Analysis System (SAS) software. C/N ratio of the compost product for windrow system reduced from 20 to 17 and from 18 to 9 for bioreactor system, with the maturity index of 7 based on Solvita test kit. Germination test was carried out with 80% success compared to the control. The NPK ratio of the biocompost produced for windrow and bioreactor systems were 2.1: 0.49: 0.59 and 3.01: 0.27: 0.68 respectively, which showed that the compost from bioreactor system was better to be used on planting trial for the ornamental plant. The heavy metals content and pathogenic microorganisms content in the final compost from both systems were within the US EPA standard and SIRIM Malaysia standard. For planting trial, there is no significant difference in terms of the physical appearance of T. erecta between different applied fertilizer treatments. However, in terms of statistical analyses, there are significant differences between the applied fertilizer treatments for the growth performance of T. erecta, the effect on the plant tissue analyses and soil, before and after treatment applied for both biocompost from windrow and bioreactor systems. The results of the present study clearly demonstrate that biocompost from municipal sewage sludge and landscaping waste produced from both windrow and bioreactor systems can be used as fertilizer for the ornamental plants.